PENGARUH PEMBERIAN SILASE RUMPUT GAJAH ODOT (Pennisetum purpureum cv. Mott) TERHADAP KONSUMSI PAKAN KAMBING BOERKA DI DESA SANDA KABUPATEN TABANAN BALI - M. B., KETAREN; DOLOKSARIBU, L.; DUARSA, M. A. P. (Majalah Ilmiah Peternakan, 2022)
The purpose of this study was to find out the effect of feeding dwarf elephant grass (Pennisetum purpureum cv. Mott) silage with different levels on body weight, consumption of forage, and level of blood glucose of boerka goats reared in Sanda Village, Tabanan Regency, Bali. This research was carried out at a boerka goat farming started from the 1st of March – the 31st of May2021. Total of 12 goats used in this study that were fed forage 10% of individual body weight daily. The method used was a completely randomized design (CRD) with three treatments, namely: forage only (P0), forage + 250 g/head/day dwarf elephant grass silage (P1), forage +750 g/head/day dwarf elephant grass silage (P2). Each treatment had 4 replications. The observed variables were: daily consumption of dwarf elep- hant grass silage, daily forage consumption, body weight, and blood glucose level. The results showed that the tre- atment (P0, P1, P2) had initial body weight of 32, 58, 21,95 and 35,10 kg, final body weight of 33.69; 23.15; 39.45 kg, daily, total forage feed consumptions were 994, 1000, 995 kg, forage feed consumptions were 4.439, 4.465, 4.444 g/head/day and total blood glucoses were 91.25, 96.83, 94.83 mg/dl. Data analysis proved that supplementary of dwarf elephant grass silage had effects between treatments (P>0.05). In summary, the supplementary of dwarf elephant grass silage higher results on forage consumptions, body weights and blood glucose levels.